Rapid detection of carbapenem resistance genes using multiplex LAMP and melt curve analysis in clinical specimens - Naik, Vaishnavi V; Kumar, Sumit; Thrimurthy, Tejal; Channareddy, Vani; Shaw, Tushar (The Journal of Infection in Developing Countries, 2026)
Introduction: Carbapenem-resistant Enterobacteriaceae have become a major clinical and public health challenge due to the need for rapid administration of effective antimicrobials and implementation of supplemental infection control practices. Identifying genes associated with carbapenem resistance is crucial for managing these cases. The timely initiation of effective antimicrobial therapy and infection control interventions to prevent spreading are critical. Therefore, rapid diagnostic tests for detecting carbapenemase-producing carbapenem-resistant Enterobacteriaceae (CP-CRE) are necessary. Methodology: This study aimed to evaluate the use of LAMP and melting curve analysis in real-time polymerase chain reaction (RT-PCR) to identify carbapenem resistance genes New Delhi metallo-β-lactamase (NDM) and oxacillinase (OXA) in clinical specimens. Results: This study emphasized the benefits of the LAMP strategy in comparison to traditional methods, demonstrating its effectiveness and practicality. LAMP was proven to be more sensitive than RT-PCR and conventional multiplex PCR, with a detection rate of 96.7% and 91.6% respectively. While LAMP had a slightly lower specificity rate of 88.7%, it remains a promising method for rapid and accurate identification. Furthermore, the study found that LAMP could detect bacterial DNA even in low quantities, with a limit of detection of 102 CFU/mL for both K. pneumoniae and E. coli. This capability is crucial for early diagnosis and treatment in settings where multidrug-resistant (MDR) bacteria are prevalent. Conclusions: RT-PCR systems that combine melting curve analysis with LAMP offer promise for quick and precise identification of carbapenem resistance genes in clinical specimens. This approach can enhance the diagnosis and management of multidrug-resistant bacterial infections.